Virtual escapes: exploring the effects of nature-based VR environments during academic breaks - Mohammed Shobri, Nor Izana; Md Dahlan, Farhan (2025)
Mental health issues among students attending lectures pose a significant concern, potentially negatively impacting their academic performance and overall well-being. Recent years have seen an increasing interest in the potential advantages of immersive nature experiences for psychological wellbeing, particularly among students in educational environments. However, there is a limitation of research examining the effect of the natural environment on students during their class breaks. Therefore, the objective of this study is to evaluate the restorative effect of natural environments video on students during their class break. This study employs a questionnaire survey to assess the restorative outcome scale and involves 140 students from the public universities in Malaysia. The video intervention was tested using a nature environment setting. Data were analysed using descriptive statistics, focusing on the mean. The results showed that students reported a relatively high level of restoration. These findings suggest that natural environment video can be beneficial in addressing mental health challenges during class breaks.